Solving Higher-Order Fractional Differential Equations by the Fuzzy Generalized Conformable Derivatives - Atimad Harir; Said Melliani; Lalla Saadia Chadli (Applied Computational Intelligence and Soft Computing)
In this paper, the generalized concept of conformable fractional derivatives of order q∈n,n+1 for fuzzy functions is introduced. We presented the definition and proved properties and theorems of these derivatives. The fuzzy conformable fractional differential equations and the properties of the fuzzy solution are investigated, developed, and proved. Some examples are provided for both the new solutions.